Pembentukan Karakter Religius Siswa melalui Aktivitas Sholat dan Tahfidz Qur’an di SD Al-Ma’soem Bandung - Ahsani, Eva Luthfi Fakhru; Sya’adah, Laela Noor; Sabila, Mujahidah Salimatus; Nuryana, Salma; Nahar, Thohirotun (ARZUSIN, 2022)
This study aims to explain the formation of students' religious character through prayer activities and tahfidz qur'an at Al-Ma'soem Elementary School Bandung. This research use desciptive qualitative approach. The method used is the field research method with the type of field research. Data collection techniques using interview techniques, observation, and documentation. The results of this study indicate that the formation of the religious character of students at Al-Ma'soem Elementary School is carried out through teaching materials in schools and studies in dormitories. Furthermore, through exemplary which is done by giving examples to students such as refracting congregational prayers, behaving and telling the truth and memorizing the Qur'an in a muraja'ah way. Activities like this are used to be carried out in every daily activity, both through religious activities and other activities so that a religious character is formed in Al-Ma'soem Elementary School students.